Kesalahan Berbahasa dalam Surat Dinas Siswa Kelas VII MTs Sunan Drajat Sugio Lamongan - Miftahul Huda; Saidatul Wafiyah (Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe various forms of language errors in the writing aspect of official letters composed by seventh-grade students of MTs Sunan Drajat Sugio using a qualitative descriptive method. The data were obtained from fifteen official letters written by these students. Data were collected through testing, observation, and note-taking techniques, using test questions and document-based corpora as research instruments. The data analysis procedure consisted of several stages, namely data selection, error identification, classification, analysis, and conclusion drawing. The results revealed several types of errors related to spelling, including: (1) punctuation errors—comprising period errors (4 instances), comma errors (4 instances), and slash errors (2 instances); (2) capitalization errors (11 instances); and (3) preposition or prefix misuse (6 instances).